Gender Research Fellowship Programme Writeshop Report, 2-6 June 2014, Bangalore, India - Fernández, M. (Bioversity International, 2015)
From April 2013 to April 2014, Bioversity International ran a Gender Research Fellowship Programme (GRFP) that brought together five scientists from low to middle income countries (Burkina Faso, Cameroon, India, Malaysia and Kyrgyzstan). The Fellows from different disciplinary backgrounds gained skills and experience in the field using gender-responsive participatory methods to examine tree and forest management processes and forest-based livelihoods. They worked within larger project teams and received mentorship to integrate gender considerations in collaborative Bioversity and partners projects focusing on the sustainable management of forest genetic resources. One year after the GRFP’s inception workshop, the Fellows came together for a ‘writeshop’ in Bangalore to complete their data analysis, work towards preparing articles for publication and share their experiences. This report documents the key moments of the writeshop, which was co-organized by Bioversity International and the International Support Group (ISG).